Walking as a regular physical activity and its impact on individuals health and public health (descriptive review) - Al Bahli, Abdullah Abdul Rahman Mohammed; Al Henaidi, Khalid Ibrahim Abdul Rahman (Journal of medical and pharmaceutical sciences, 2018)
With the time passing and according to the enhanced reliance on technological and transportation means that decrease the level of individuals movement and the increase of the existence of several accompanied diseases with this phenomenon, the researchers must investigate the reason behind the spreading of such diseases among different society's members. The vast majority of researchers agreed that individual lifestyle is declining with their paying attention to their health food quality, quantity and content, or paying attention to their physical and social activities that contribute to making their lives better from various aspects. Several solutions have been proposed to minimize health issues that could be generated from the changes in their lifestyles. This study came to investigate the relation between walking on individuals' public health, and to find the relation between walking level on suffering from this age diseases.The research followed the descriptive approach to presenting the research problem and the recommendations for solving it. The study reviewed aseries of research that focued on the impact of walking and physicalactivity on human health and the extent to which physical activityrelates to different diseases of the age.The results of the study showed that walking has a positive effect onthe whole, whether it is the disease or the prevention of the expecteddiseases. It also has positive effects on the health of the differentbodies of the body. Walking has good effects on the psychologicaland cognitive health of the individual. The study also recommendedchanging lifestyles and encouraging individuals to walk by removingthe appropriate means they need to walk, groups and clubs tostimulate walking within groups.
Keywords: walking; health; age diseases; physical activity